2016
DOI: 10.1108/nfs-12-2015-0157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different thistle flower ecotypes as milk-clotting in Serra da Estrela cheese

Abstract: Purpose Thistle flower (Cynara cardunculus) aqueous extracts, as rich source of milk-clotting peptidases, have been widely used for cheeses marketed under the Registry of the Protected Designation of Origin, as it is the case of Serra da Estrela cheese, manufactured from raw ewes’ milk and without addition of any commercial starter culture. This paper aims at studying the influence of six different ecotypes of thistle flowers in cheese properties during the ripening and of final products. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…In the past, two decades ago, an approach used to improve the microbiological quality was to manufacture Serra da Estrela cheeses with addition of distinct starter cultures isolated from the native microbiota of raw milk cheeses; however, those cheeses exhibited a more acid and bitter flavors than the traditional cheese (Macedo et al, ). More recently, the sensorial properties of Serra da Estrela cheeses were evaluated in regards to the thistle ecotype used, production location, dairy, and ripening time having the cheese paste creaminess and the rind hardness presented significant differences in cheeses made by different producers and with different thistle ecotypes (Correia et al, ; Guiné et al, ).…”
Section: Sensorial Attributes and Texturementioning
confidence: 99%
See 1 more Smart Citation
“…In the past, two decades ago, an approach used to improve the microbiological quality was to manufacture Serra da Estrela cheeses with addition of distinct starter cultures isolated from the native microbiota of raw milk cheeses; however, those cheeses exhibited a more acid and bitter flavors than the traditional cheese (Macedo et al, ). More recently, the sensorial properties of Serra da Estrela cheeses were evaluated in regards to the thistle ecotype used, production location, dairy, and ripening time having the cheese paste creaminess and the rind hardness presented significant differences in cheeses made by different producers and with different thistle ecotypes (Correia et al, ; Guiné et al, ).…”
Section: Sensorial Attributes and Texturementioning
confidence: 99%
“…The combination of these methods, RAPD‐SCAR can be used to prevent fraudulent Serra da Estrela PDO cheese production and be implemented as a quality control. Innovations are also associated with the possibility to manipulate the final texture/sensory profile of Serra da Estrela cheese mainly via the thistle ecotype selected (Correia et al, ; Guiné et al, ). The genotype evaluation of selected cardoons has been performed in order to improve the quality and standardization of cardosin profiles from cardoon flowers used for cheese production (Barracosa, Rosa, Barros, & Pires, ), having the different cardoon cultivars been morphologically evaluated (Barracosa, Oliveira, Barros, & Pires, ).…”
Section: Innovation Concerning Serra Da Estrela Cheesementioning
confidence: 99%
“…The evaluation of individual genotypes showed that the observed biodiversity is also reflected in the amount and type of APs present in the flowers of each genotype, with enzymes present in some genotypes and absent in others [16]. This variability was also found to affect the milk-clotting process, as the use of flower extracts from different thistle populations displayed different milk-clotting times, which ultimately affected cheese manufacturing and the rheological and sensorial characteristics of the final product [17,18]. Thus, the use of thistle flower extracts as milk-clotting agents is dependent upon the presence and specific activities of different APs.…”
Section: The Thistle Flower and The Impact Of Its Variability On Milkmentioning
confidence: 99%
“…Serra da Estrela (SE) cheese is a Portuguese traditional agro-food product with Protected Designation of Origin (PDO), manufactured only from raw ewe's milk (exclusively from Serra da Estrela sheep), cardoon flower (Cynara cardunculus L.) and salt [1][2][3]. SE cheese is perceived as a unique high-quality food product with great economic importance [4,5], highly appreciated for its strong aroma, slight bitterness and semi-soft texture [6]. The cheese final properties are dependent on a variety of parameters, including the characteristics of used ingredients and processing factors.…”
Section: Introductionmentioning
confidence: 99%